(untitled) (Ameghiniana, 2013)
Seventeen species of pollen grains are described and illustrated. They belong to the following genera: Podocarpidites, Microcachrydites, Araucariaciies, Cycadopites, Entylissa, Liliacidites, Tricolpites, Rousea, P silatricolpites, M omipites, Triporopollenites, Triatriopollenites and Anacolosidites. The statistical study reveals that the microflora was deposited in a transitional enviromnent, characterized by humid conditions. The latter are indicated by the high fresquencies of trilete and monolete spores and monosulcate grains.